Betaine Dietary Supplementation: Healthy Aspects in Human and Animal Nutrition - Giovanni Buonaiuto; Alessia Federiconi; Carla Giuditta Vecchiato; Elisa Benini; Attilio Luigi Mordenti (Antioxidants, 2025)
Betaine, a naturally occurring compound primarily derived from sugar beet by-products, has attracted increasing attention for its multifaceted roles in human and animal nutrition. Acting as both an osmolyte and a methyl group donor, betaine contributes to cellular hydration, methylation balance, antioxidant defense, and metabolic regulation. This review provides a comprehensive overview of betaine’s biological functions and its health-promoting effects across species. In humans, betaine supports hepatic function, cardiovascular health, renal protection, and physical performance, mainly by modulating homocysteine metabolism, lipid profiles, and oxidative stress. In animal production systems, it enhances growth, feed efficiency, reproductive performance, and resilience to heat stress, with species-specific applications in monogastrics, ruminants, aquaculture species, and companion animals. The review also explores the molecular mechanisms underlying betaine’s effects, including epigenetic regulation and mitochondrial function, and presents updated evidence on its biosynthesis, bioavailability, and nutrient interactions. Furthermore, the use of betaine derived from agro-industrial by-products aligns with the principles of the circular economy, promoting the sustainable reuse of valuable compounds within the agri-food chain. Despite promising findings, further research is needed to standardize effective dosages and clarify species-specific responses under different physiological and environmental conditions. Overall, betaine emerges as a promising and sustainable functional ingredient with wide-ranging applications in nutrition and health.